Use of Ergonomics to Control Musculoskeletal Pain among Dental Students at King Abdulaziz University: A Cross-sectional Study - Sabbagh, Heba J. (Journal of King Abdulaziz University: Medical Sciences, 2022)
The prevalence of musculoskeletal pain (MS-Pain) increases day by day and is common among dental practitioners. The aim of this study was to assess the relationship between ergonomics use and other related factors in controlling musculoskeletal pain among dental students and interns at King Abdulaziz University, Jeddah, Saudi Arabia. This cross-sectional study was conducted at King Abdulaziz University through a validated self-administered questionnaire. It was distributed among dental students from the fourth academic year up to postgraduate level. The total number of respondents was 402, in which 202 (50.2%) were females and 200 (49.8%) were males. Out of the total respondents, 337 (83.8%) reported musculoskeletal pain and approximately 68% of respondents did not apply proper ergonomics for preventing and reducing MS-Pain. Keeping a straight back and maintaining physical activity are the two main factors that are suggested to help in controlling MS-pain, and thus it needs to be emphasized in the everyday clinical educational years